Clinician education unlikely effective for guideline-adherent medication prescription in low back pain: systematic review and meta-analysis of RCTs. (January 2022) - Belavy, Daniel L; Tagliaferri, Scott D; Buntine, Paul; Saueressig, Tobias; Sadler, Kate; Ko, Christy; Miller, Clint T; Owen, Patrick J
Summary: Background: Effectiveness of implementing interventions to optimise guideline-recommended medical prescription in low back pain is not well established. Methods: A systematic review and random-effects meta-analyses for dichotomous outcomes with a Paule-Mandel estimator. Five databases and reference lists were searched from inception to 4 th August 2021. Randomised controlled/clinical trials in adults with low back pain to optimise medication prescription were included. Cochrane Risk of Bias 2 tool and GRADE were implemented. The review was registered prospectively with PROSPERO (CRD42020219767). Findings: Of 3352 unique records identified in the search, seven studies were included and five were eligible for meta-analysis (N=11339 participants). Six of seven studies incorporated clinician education, three studies included audit/feedback components and one study implemented changes in medical records systems. Via meta-analysis, we estimated a non-significant odds-ratio of 0·94 (95% CI (0·77; 1.16), I² = 0%; n=5 studies, GRADE: low) in favour of the intervention group. The main finding was robust to sensitivity analyses. Interpretation: There is low quality evidence that existing interventions to optimise medication prescription or usage in back pain had no impact. Peer-to-peer education alone does not appear to lead to behaviour change. Organisational and policy interventions may be more effective. Funding: This work was supported by internal institutional funding only.